Predictors of spinal cord stimulation success - De La Cruz, Priscilla (Neuromodulation, 2015)
INTRODUCTION: As many as 30% of SCS patients fail to obtain long term pain coverage, even with the strictest parameters of a successful trial, unremarkable psychological assessment, and ideal placement of the permanent device. Why these patients either never receive adequate benefit or lose benefit remains elusive. METHODS: We perform a retrospective review of our prospective database of SCS patients undergoing surgery for routine indications. Six month post-operative follow-up data was available for 57 patients. Two providers who routinely saw the patients were asked to independently grade the patient’s outcome in a blinded fashion on a Global Outcome Ratings scale of 1 to 10, with 5 being 50% improvement at six months post-operation. A score of less than 5 was deemed a failure. The impact of Body Mass Index (BMI), random drug screen results, workers’ compensation status, depression, and smoking were assessed. RESULTS: We report a phi correlation of 0.350 between smoking and failure (p=0.017). Smoking status is correlated with both lead migration revisions (phi =0.269) (p=0.044) and with revision due to new pain symptoms (phi=0.241) (p=0.072). Further, there is a trend of correlation (phi=0.289) between drug use and patients (n=3) who underwent device removal (p=0.045). In this cohort, worker’s compensation status, BMI, and depression did not impact outcome. CONCLUSIONS: Tobacco use correlates with less success with SCS at 6-month follow-up. Whether that is because of issues with healing and our transmission of signals to the periphery warrants further exploration. This data provide further evidence that tobacco cessation is important to surgical results.